The beginnings and development of arms research in Łódź - Głosek, Marian (Armia kontra natura, 2020)
The article discusses the beginnings of arms research in the Łódź center. It should be noted that the author only took up research on the most interesting period: the Middle Ages and early modernity. These studies were carried out in three centers – the Institute of Archeology of the Polish Academy of Sciences, the Institute of Archeology and the Institute of History of the University of Łódź. The main subject of these studies is combat and ceremonial weapons, weapon signatures, ornamentation, production, arsenal resources, trade, use of weapons on the battlefield and organization of the army. Research focused on the Polish military, but studies on armaments from Central Europe were also successfully undertaken. Research on the military of the Teutonic Order and the armament of the Nomads was also has been conducted in Łódź. This research was initiated by Professor Andrzej Nadolski, who created the “Łódź School of Arms” and became an inspiration for research for many military historians.